Experimental characterization of the compressive and shear behavior of square cell titanium honeycomb - Parsons, Ryan Tyler (Kansas State University, 2009)
The purpose of this study was to experimentally characterize the compressive and shear behavior of square cell titanium honeycomb cores according to the American Society of Testing and Materials Standards C 365-05 and C 273-06. By varying the honeycomb cell size and height as well as the foil thickness, many configurations of titanium honeycomb were manufactured utilizing a laser welding and expansion method. The test matrix consisted of 1080 compression and 1080 shear specimens. The compression specimens were split evenly into stabilized and unstabilized tests, and the shear specimens were split evenly to test three different shear orientations. At the conclusion of the characterization, a comprehensive statistical analysis was performed on the data. It was determined that both the compressive and shear strengths have a strong dependence on the relative density of the honeycomb. The compressive strength was found to be slightly affected by the presence of a stabilizing face sheet, and largely unaffected by specimen core height. The compressive modulus was affected by both the core height and the presence of a face sheet. Shear strength was found to decrease with increasing core height and was influenced by the shear orientation. Additionally, the rate of increase of shear modulus with respect to relative density was proportional to core height. Although no clear trend was observed, orientation did seem to have an effect on shear modulus. The compression and shear behavior of the honeycomb was compared with experimental results of honeycomb from existing publications and found to be consistent.
Keywords: Honeycomb; Titanium; Compressive; Shear; Experimental; Properties; Engineering, Materials Science (0794); Engineering, Mechanical (0548)